Pelatihan Pemberdayaan Perempuan Mantan TKI Melalui Pelatihan Strategi dan Keuangan Bisnis - Rifka Arinda Noviasari; Achmad Iqbal; Priangga Eko Saputra; Wiwik Mukholafatul Farida (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Migrant workers, also known as Indonesian Migrant Workers (TKI), are one of the professions that many Indonesians choose. The reasons are varied, ranging from a lack of jobs in the country to economic reasons because the salaries of TKI are quite high. Problems arise when migrant workers have returned to their homeland and start managing businesses (MSMEs). Empowerment training for former TKI women through business strategy and finance training is urgently needed. So that the University of 17 August 1945 Banyuwangi collaborated with Migrant Care to conduct training. Through the FGD method, interactive lectures, and mentoring, the training conducted resulted in participants' understanding regarding business strategy (Cost Leadership, Differentiation, Focus) that will be applied in their business. In addition, participants also know basic accounting and how to calculate HPP and how to do a Break Even Point (BEP) analysis. Through mentoring, the participants have also been able to create financial position reports and profit/loss reports for their respective MSMEs.